PEMBUATAN SISTEM PEMANTAUAN PH DAN PPM AIR PADA HIDROPONIK BERBASIS IoT - Agus Hermanto; Tony Ahmad Husein Al Mubarok; Agung Kridoyono (Jurnal Sistem Informasi dan Informatika (Simika), 2025)
The reduction in agricultural land due to being converted into housing and urban areas means that the amount of food production is decreasing. Based on the problems above, the author offers an innovation to overcome the problem of food security through "Smart Farming". This innovation can be implemented by the community using the concept of integrated agriculture with fisheries which is easy to apply on minimal land which has not been utilized properly. However, currently There is currently no system that can monitor the pH and PPM levels of water automatically and easily. This has an impact on the poor quality of hydroponic plant production so that it cannot be sold to consumers and causes losses for this business Internet of Things (IoT) and website, this smart farming innovation was developed as a system for monitoring the condition of pH and PPM levels of water in hydroponic planting media. The development of a website-based pH and PPM monitoring system offers an innovative approach in utilizing technology to overcome the challenges of monitoring water quality effectively. By utilizing the advantages of information technology and the internet, this system can become an important solution in supporting efforts to protect the environment and sustain water resources in the future.